Current Adenosinergic Therapies: What Do Cancer Cells Stand to Gain and Lose? - Kotulová, Jana; Hajdúch, Marián; Džubák, Petr (International journal of molecular sciences, 2021)
A key objective in immuno-oncology is to reactivate the dormant immune system and increase tumour immunogenicity. Adenosine is an omnipresent purine that is formed in response to stress stimuli in order to restore physiological balance, mainly via anti-inflammatory, tissue-protective, and anti-nociceptive mechanisms. Adenosine overproduction occurs in all stages of tumorigenesis, from the initial inflammation/local tissue damage to the precancerous niche and the developed tumour, making the adenosinergic pathway an attractive but challenging therapeutic target. Many current efforts in immuno-oncology are focused on restoring immunosurveillance, largely by blocking adenosine-producing enzymes in the tumour microenvironment (TME) and adenosine receptors on immune cells either alone or combined with chemotherapy and/or immunotherapy. However, the effects of adenosinergic immunotherapy are not restricted to immune cells; other cells in the TME including cancer and stromal cells are also affected. Here we summarise recent advancements in the understanding of the tumour adenosinergic system and highlight the impact of current and prospective immunomodulatory therapies on other cell types within the TME, focusing on adenosine receptors in tumour cells. In addition, we evaluate the structure- and context-related limitations of targeting this pathway and highlight avenues that could possibly be exploited in future adenosinergic therapies.
Keywords: immuno-oncology; Molecular Targeted Therapy; cílená molekulární terapie; lidé; adenosine receptors; imunoterapie; purinergní receptory P1; karcinogeneze; Adenosine; Tumor Microenvironment; adenosinergic therapy; Humans; cancer; adverse effects; Receptors, Purinergic P1; Immunotherapy; nádorové mikroprostředí; immunosurveillance; nádory; adenosine; zvířata; Carcinogenesis; Animals; adenosin; Neoplasms; tumour microenvironment